62.2k views
1 vote
-6(-4u+4)-6u=2(u-5)-8

1 Answer

5 votes

Answer:

u=0.375

Explanation:

First we can write the equation down, -6(-4u+4)-6u=2(u-5)-8. First what you want to do is distribute -6 to (4u+4) and 2 to (u-5). This would result in 24u-24-6u=2u-10-8. Next add up all like terms and you will get 18u-24=2u-18. Next you would want to add 24 on both sides so that you get 18u=2u+6 then subtract 2u from both sides to get 16u=6. You the divide 16 on both sides to get u=0.375.

User Balint Domokos
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.